COMMUNITY PARTICIPATION IN PREVENTING THE SPREAD OF SMOKING HABITS IN THE SURROUNDING ENVIRONMENT - Farrel Erlangga Tarigan; Khairunisa Hasanah BR. Simatupang; Naufal Afif Raditya Banurea; M. Daffa Hendry Desky (PT. Radja Intercontinental Publishing, 2025)
The prevalence of smoking in Indonesia is very high and has become a public health problem. According to 2023 WHO data, the proportion of cigarettes among the adult population (15+) in Indonesia reached around 34.5%. To address this, the role of the community is essential as a proxy for behavior change. This study reviewed literature and secondary data (WHO, the Indonesian Ministry of Health, BPS, and academic studies) to understand how local community involvement can prevent the spread of smoking. The research method used was a descriptive qualitative study with content analysis of quantitative and qualitative data. The results of the study indicate that community empowerment programs such as anti-smoking campaigns involving community leaders and community-based health education raise awareness and change social norms about smoking (Halim et al., 2024; Sugiyo & Sutrino, 2021). For example, the